2021
DOI: 10.1080/1540496x.2021.1873764
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Economic Uncertainty in China

Abstract: This study develops a new economic uncertainty (EU) index based on Chinese newspapers to address the media coverage bias of existing measures. We investigate how EU affects China's macroeconomy. Our results suggest that EU reduces aggregate output. We find that uncertainty predicts fluctuations in economic activity and actual economic activity also predicts EU, but nonlinearly. Furthermore, we show that uncertainty in the United States leads to uncertainty in China, implying that negative EU on the Chinese eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…In terms of growth, the effect of economic policy uncertainty (EPU) on economic growth is found to be negatively significant, especially for Asian countries (Lensink, Bo and Sterken, 1999; Xu et al 2021 ; Pan et al 2021 ). Interestingly, monetary uncertainty was found to be less severe than fiscal uncertainty, where fiscal uncertainty generally relates to government expenditures, taxes, budget deficits and sales uncertainty.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of growth, the effect of economic policy uncertainty (EPU) on economic growth is found to be negatively significant, especially for Asian countries (Lensink, Bo and Sterken, 1999; Xu et al 2021 ; Pan et al 2021 ). Interestingly, monetary uncertainty was found to be less severe than fiscal uncertainty, where fiscal uncertainty generally relates to government expenditures, taxes, budget deficits and sales uncertainty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In spite of the growing literature on the effects of uncertainty on economic activities (e.g. Altig et al 2020 studied US and UK; Lin and Bai 2021 ; Xu et al 2021 ; and Pan, Wang and Wang, 2021 studied China), empirical evidence in Africa remains scanty, especially following the ongoing Covid-19 Pandemic. Besides, the moderating effect of governance institutions on the uncertainty-economic performance relationship in Africa is yet to be accounted for.…”
Section: Introductionmentioning
confidence: 99%
“…Financial events are one of the important components of structural changes in the stock market. The prior literature has found that the split share structure reform in September 2005 showed its impact on the Chinese stock market's asset price by shareholders' bargaining power [19,20]; the global financial crisis in 2008 had an impact on the A-share stock market due to the global trade network [21,22]; and the margin trading and short selling mechanism in March 2010 also narrowed the A-share asset price premium by providing the margin buying and short selling opportunities [23]. Therefore, we propose that Hypothesis 3 (H3): Financial events can affect the significance of excess return of the portfolio.…”
Section: Hypothesis 1 (H1)mentioning
confidence: 99%
“…While these policies prevented a sharp economic downturn, the frequent adjustment of macro-policy environments led to ambiguous and unpredictable government policy directions, resulting in significant EPU [23,24]. In China, the annual average value of the EPU index in 2020 was 13.39 times that in 2000 [25], leading to increased risks in market operations, exacerbated capital outflows, and economic turbulence [26]. Such factors affect enterprises' sensitivity to economic policies and influence their technological innovation activities.…”
Section: Introductionmentioning
confidence: 99%